Dati territoriali e metodi di governance digitale in un'esperienza di pianificazione costiera comunale - Pasquale Balena (mediaGEO soc. coop., 2021)
Contemporary practices in Integrated Coastal Zone Management (ICZM) show trends of co-evolving digital technologies and organizational learning. Within this framework, spatial data infrastructures are proving key, on the one hand, in enabling ecosystem-based management approaches while, on the other hand, in supporting the growing role that local authorities play in coastal governance. In this paper, we report on the preliminary outcomes of a research and innovation collaboration between the municipality of Rodi Garganico (located in Southern Italy) and the Polytechnic University of Bari (Italy). The work concerned the application of geospatial technologies to the local coastal plan-making process and helped shed lights on both persisting challenges to, and promising prospects of, ICZM.